Students' Needs for Autonomous Learning through Self-Access Center Resources and Activities: A Survey on the Target and Learning Needs of SAC Users - Mukamil Mukamil; Slamet Asari; Nirwanto Ma’ruf; Bayu Hendro Wicaksono (Universitas Muhammadiyah Gresik, 2023)
The Self-Access Center (SAC) is one of the infrastructures for realizing the self-access approach as one of the modes of learning beyond the classroom (LBC) that is essential to the manifestation of the student-centered approach in language education. This study looked at the target needs of English department students for independent learning using SAC resources and their learning needs for independent learning using SAC activities. There were 51 university students participated in the study using a mix of questionnaire and interview data collection techniques. The study revealed that the student's primary necessity for autonomous learning resources of SAC was materials for specific English skills out of the classroom supported with the use of sufficient internet resources and a native speaker as a resource. It is to fulfill their short and long terms goals to attend in SAC. It was also discovered that the students preferred individual reading, free writing, native American speaker advisors, and listening activities. Vocabulary, pronunciation, and grammar need to be progressively integrated into these programs since many of them wish to be overseen by Native American speakers, notably for the American English pronunciation model, and non-native speakers for English grammar.